A Receiver Perspective on Knowledge Sharing Impact on Consumer–Brand Relationship in Virtual Communities - Zhang, Jiemei; Qi, Shaojing; Lyu, Bei (Frontiers in Psychology, 2021)
The virtual community offers groups of consumers a knowledge-shared platform, wherein shared brand information influences others’ brand cognition. Using stimulus–organism–response (SOR) model, this paper constructs a research framework for the influence of knowledge-sharing on consumer–brand relationship in virtual communities. The empirical analysis shows that knowledge-sharing quality has significant positive effects on the sense of virtual community, as does the sense of virtual community on the consumer–brand relationship. This paper supports strengthening of consumer–brand relationship and the enrichment of following research on consumer’s knowledge-sharing in virtual communities. Thus, companies should encourage consumers to actively participate in brand activities, and focus on the development of consumer–brand relationship during the course of participation for brand promotion.